Spinocerebellar ataxia type 2 presenting with involuntary movement: a diagnostic dilemma - Shu-Ting Li; Yang Zhou (Journal of International Medical Research, 2019)
Spinocerebellar ataxia type 2 (SCA2) is a rare disease characterized by slowly progressive ataxia, dysarthria, ophthalmoplegia, and slow saccade. SCA2 can present with a complex combination of hyperkinetic and hypokinetic movement disorders. Here, we describe a patient with SCA2 that partly mimicked the clinical manifestations of Huntington’s disease; similar symptoms had previously occurred in the patient’s family members. The findings in this report indicate that, when a patient exhibits choreiform movement (i.e., accompanying cerebellar ataxia), an SCA2-related mutation could be responsible for the onset of disease. In addition, this knowledge of the potential for extrapyramidal involvement in such patients is critical for clinicians.